STRENGTHENING INNOVATION AND STANDARDIZATION OF WAHYU ALAM HERBAL MEDICINE PACKAGING IN ENTERING THE GLOBAL MARKET - Puspita, Nindi Vaulia; Gasimov, Elchin; nurlaely; Dewandaru, Bothy (Jurnal Abdi Masyarakat, 2025)
This community service activity aims to increase the competitiveness of Jamu Wahyu Alam products through packaging standardization and innovation so they can penetrate the global market. Partners' problems include limited knowledge of international packaging standards, difficulties in designing and selecting environmentally friendly materials, and limited resources for promotion. The solutions offered are training, workshops, and mentoring related to packaging standardization, modern design innovations that also represent traditional values, and the use of environmentally friendly packaging materials according to global trends. The activity was carried out in the form of a one-month training that included needs analysis, prototype design, evaluation, and packaging finalization. The results of the activity showed an increase in partners' knowledge and skills in understanding international packaging standards, global consumer-oriented designs, and digital marketing strategies. Thus, this activity successfully helped partners in strengthening product quality, increasing sales value, and expanding international market opportunities for the local herbal medicine industry